A review of UV radiation protection on humans by textiles and clothing. Issue 6 (13th May 2020) - Khan, Asfandyar; Nazir, Ahsan; Rehman, Abdur; Naveed, Maryam; Ashraf, Munir; Iqbal, Kashif; Basit, Abdul; Maqsood, Hafiz Shahzad
Abstract : Purpose: This review deals with the pros and cons of ultraviolet (UV) radiation on human beings and the role of textile clothing and the chemicals used for textiles to protect from their harmful effects. Design/methodology/approach: UV radiation (UVR) which has further divided into UVA, UVB, and UVC. Almost 100% of UVC and major portion of UVB are bounced back to stratosphere by ozone layer while UVA enters the earth atmosphere. Excessive exposure of solar or artificial UVR exhibit potential risks to human health. UVR is a major carcinogen and excessive exposure of solar radiation in sunlight can cause cancer in the lip, skin squamous cell, basal cell and cutaneous melanoma, particularly in people with the fair skin. Findings: This article aims to provide a comprehensive overview of the harmful effects of UVR on human skin, factors affecting UV irradiance and factors affecting UV protection offered by textile clothing. Originality/value: Effect of fiber properties, yarn properties, fabric construction, fabric treatments and laundering has been reviewed along with the identification of gaps in the reported research. A comparison of inorganic and organic UV absorbers has also been given along with different testing and evaluation methods for UV protective clothing.